4.2: External compensation Type OLED Panel Using Novel Gate Driver Circuit with Depletion‐Mode IGZO TFTs. (26th August 2021) - Feng, Xuehuan; Li, Yongqian; Yuan, Can; Yuan, Zhidong; Xu, Pan; Meng, Song; Wei, Xiaolong; Bao, Wenchao; He, Ming; Liu, Fengjuan; Wu, Zhongyuan; Yu, Jianwei; et al.
Abstract : A novel gate driver circuit was shown in this paper which was prepared for 55inch 8K4K OLED panel. The new schematic can realize display images and sensing TFT characteristics for external compensation. At high temperature (50 °C) companied with high humidity (80% RH) this circuit could work normally for more than 500 hours based on 5 inch experiment panels. And at very low temperature (‐20 °C) our panel also had a well performance. Besides, this novel GOA (Gate driver on array) circuit can make our future 55inch panel to achieve a narrow bezel smaller than 8mm